Brain mechanisms of pain relief by transcutaneous electrical nerve stimulation: A functional magnetic resonance imaging study. (2nd April 2015) - Choi, J.C.; Kim, J.; Kang, E.; Lee, J.‐M.; Cha, J.; Kim, Y.J.; Lee, H.G.; Choi, J.‐H.; Yi, D.‐J.
Abstract: Background: Although the exact mechanism of TENS pain relief is unknown, it is believed that TENS impulses interrupt nociceptive signals at the dorsal horn of the spinal cord. Aims: To evaluate the hypotheses that during pain caused by noxious stimuli, brain responses, temporal summation and brain functional connectivity are modulated by TENS, and that mechanisms of pain relief by TENS differ between men and women. Methods: During fMRI scanning, the same noxious stimuli were delivered to each participant in pain‐only and pain+TENS conditions. In the pain‐only condition, noxious stimuli were presented without TENS. In the pain+TENS condition, participants received noxious stimuli and TENS concurrently. Participants were initially presented with TENS at an intensity that was just below that causing discomfort. TENS intensity was presented in a step‐wise fashion to prevent temporal summation from repetitive noxious stimuli. Results: Pain and unpleasantness ratings were significantly higher in the pain‐only than the pain+TENS condition. With non‐painful TENS, primary and secondary somatosensory and parietal cortices were activated, and temporal summation from repetitive noxious stimuli was prevented. Periaqueductal gray (PAG) and lateral prefrontal cortex functional connectivity was increased by TENS, and modulated by testosterone and cortisol. Women reported greater pain during TENS than men, and showed greater activation in the temporoparietal junction cortex and increased PAG functional connectivity with the orbitofrontal cortex. Conclusion: TENS led to pain reduction, probably due to activation of the descending pain‐inhibitory pathway, indicating that this TENS method may be applied in clinical practice.